Feasibility study: highly integrated chipset design for compact synthetic aperture radar payload on micro-satellite. Issue 6 (13th April 2017) - Wang, Yong; Ye, Wenbin; Hong, Yan; Cao, Yuan; Zheng, Yuanjin
Abstract: Micro- and nano-satellites are attractive due to the low development and launching costs. Carried by micro- and nano-satellites, synthetic aperture radars (SARs) have great potential for urban, oceanography, land use, and agriculture usages. Different than conventional satellites, the payload of micro- and nano-satellites is limited. This imposes great challenges on the SAR system design. Traditional SARs adopt thousands of millimeter-wave integrated circuit (MMIC) components; they are bulky and power hungry. This paper investigates the feasibility to deploy the emerging technologies to shrink the volume, reduce the cost, and improve the power efficiency of the SAR system. Highly integrated radar transceiver integrated circuits (ICs) are reviewed, and an SAR transceiver IC is developed. Design technologies of low-noise amplifiers (LNAs) and high-power amplifiers (HPAs) are compared, and Gallium Nitride (GaN) technology is proposed. A novel microelectromechanical system-based delay line is also proposed for satellite SAR to reduce the system size. Existing issues and expected improvements of these technologies are also elaborated. This work shows a clear route map for the future shrinkage of SAR system, and would be a useful guideline to the development of compact SARs for micro-satellites.